Web accessibility in on-line learning in information science: a systematic review of the brazilian literature on Brapci - Nakano, Natalia [UNESP] (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2022)
Introduction: The revolution brought about by information and communication technologies and the Internet has transformed the way people seek and get information and build knowledge. in order to keep up with society's demands, institutions and legislation also had to adapt to the new informational reality, using digital environments, especially to provide access to public information aiming at transparency, and for training purposes in virtual learning environments. For all citizens, without discrimination, to participate and benefit from these environments with equality, digital environments must be accessible. In this context, the aim of this article is to investigate the state of the art on the theme Web accessibility in the field of Information Science in the national literature. Method: For this, the Systematic Literature Review in the Reference Database of Journal Articles in Information Science was used. Results: The research results point to the concern of the area in studies that conduct a dialogue between the theme accessibility and Information Science: that point out the barriers to accessing information on digital platforms; and that discuss accessibility in view of the legislation in Brazil. Conclusion: The study concluded that it is necessary to consider the community and human issues involved in the dynamics of the access and accessibility process in digital environments, such as knowledge about assistive technology and Internet browsing and the informational need of people with disabilities, in addition to knowledge about access and accessibility by the team developing the digital environment.
Keywords: Information and Technology; Information Design; Accessibility; Access to information; Systematic Literature Review